2011
DOI: 10.1038/hr.2011.203
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure variability in relation to autonomic nervous system dysregulation: the X-CELLENT study

Abstract: The purpose of this study was to investigate the association of autonomic nervous system dysregulation with blood pressure variability. Among the 2370 participants in the X-CELLENT study, 577 patients (59.0±10.2 years) were randomly selected to participate in an ancillary ambulatory blood-pressure monitoring study. We proposed a novel autonomic nervous system regulation index termed dSBP/dHR, which was defined as the steepness of the slope of the relationship between the 24-h systolic blood pressure (SBP) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 17 publications
4
16
1
Order By: Relevance
“…It is possible that elderly individuals with lower BPV may have less BP reduction and thus experience reduced consequences of orthostatic hypotension. It is important to note that many studies reported that high BPV is associated with autonomic dysfunction; however, we did not find any studies performed in the elderly and it is possible that autonomic dysfunction in the elderly may manifest differently. Another possible explanation for the apparent increased mortality in the elderly with low BPV is that in hypertensive patients, low BPV may represent a poor response to treatment or nonadherence, because, in hypertensive patients, BPV may be at least partially attributed to response to treatment.…”
Section: Discussioncontrasting
confidence: 58%
“…It is possible that elderly individuals with lower BPV may have less BP reduction and thus experience reduced consequences of orthostatic hypotension. It is important to note that many studies reported that high BPV is associated with autonomic dysfunction; however, we did not find any studies performed in the elderly and it is possible that autonomic dysfunction in the elderly may manifest differently. Another possible explanation for the apparent increased mortality in the elderly with low BPV is that in hypertensive patients, low BPV may represent a poor response to treatment or nonadherence, because, in hypertensive patients, BPV may be at least partially attributed to response to treatment.…”
Section: Discussioncontrasting
confidence: 58%
“…BP variability has been linked to autonomic dysfunction (Zhang et al, 2011) and cardiovascular mortality (Kikuya et al, 2000, 2008). Allan et al (2006) reported that orthostatic hypotension, one of the symptoms of autonomic dysregulation, might be related to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary analysis of data from the X-CELLENT study has also associated autonomic dysfunction with a heightened day-night systolic blood pressure gradient and more variable systolic blood pressure over 24 h in patients with essential hypertension [3]. In the current study we were unable to control for dietary salt intake, smoking, obesity and obstructive sleep apnea [26], factors that are known to influence reversal of circadian pattern.…”
Section: Discussionmentioning
confidence: 90%
“…Patients with OH often have abnormal 24-h ambulatory blood pressure monitoring (ABP) profile characterized by reversal of circadian pattern, postprandial hypotension, and non-compensatory heart rate variability [2]. Interestingly, heightened day-night systolic blood pressure gradient [3], increased nocturnal heart rate [4] and postprandial hypotension [5] on ABP have also been associated with dysfunction of the autonomic nervous system. The diagnosis of autonomic dysfunction requires a battery of testing that includes cardiovagal heart rate tests, laboratory indices of adrenergic function and sudomotor tests.…”
Section: Introductionmentioning
confidence: 99%